Game Programming using Qt 5 Beginner's Guide : Create amazing games with Qt 5, C++, and Qt Quick, 2nd Edition /: Create amazing games with Qt 5, C++, and Qt Quick, 2nd Edition. (2018) - Strakhov, Pavel Vladimirovich
No abstract available